2018
DOI: 10.1016/j.vetimm.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of AvBD6-10 in broiler chickens is independent of AvBD6, 9, and 10 peptide potency

Abstract: The Avian β-defensin (AvBD) gene cluster contains fourteen genes; within this, two groups (AvBD6/7 and AvBD8 -10) encode charged peptides of >+5 (AvBD6/7), indicative of potent microbial killing activities, and ≤+4 (AvBD8-10), suggestive of reduced antimicrobial activities. Chicken broiler gut tissues are constantly exposed to microbes in the form of commensal bacteria. This study examined whether tissue expression patterns of AvBD6-10 reflected microbial exposure and the encoded peptides a functional antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
7
0
3
Order By: Relevance
“…At the same time, there was a significant upregulation of AvBD10 in the challenged birds of Subgroup II in addition to an elevated expression of this gene in Subgroups III and IV. AvBD10 upregulation in response to the Salmonella bacteria in the chicken intestine was also shown in other studies [119]. Interestingly, high expression of this gene found in Subgroup III at both 1 and 7 dpi suggests a positive effect of Intebio on the AvBD10 regulation in the growing non-challenged chickens, which, in turn, could be linked to observations (as reviewed in Mowbray et al [119]) that AvBD10 may be involved not only in direct killing of the pathogens, but also in maintaining the developmental and other physiological processes as well as protective properties of cells.…”
Section: Discussionsupporting
confidence: 81%
“…At the same time, there was a significant upregulation of AvBD10 in the challenged birds of Subgroup II in addition to an elevated expression of this gene in Subgroups III and IV. AvBD10 upregulation in response to the Salmonella bacteria in the chicken intestine was also shown in other studies [119]. Interestingly, high expression of this gene found in Subgroup III at both 1 and 7 dpi suggests a positive effect of Intebio on the AvBD10 regulation in the growing non-challenged chickens, which, in turn, could be linked to observations (as reviewed in Mowbray et al [119]) that AvBD10 may be involved not only in direct killing of the pathogens, but also in maintaining the developmental and other physiological processes as well as protective properties of cells.…”
Section: Discussionsupporting
confidence: 81%
“… Xu et al (2015) also reported that, among AvBD1 to 13, all AvBDs (except for AvBD2 and 8) were expressed in the kidneys of layer chicks. Mowbray et al (2018) showed the expression of AvBD6 to 8 in the kidneys of broiler chicks from hatching to 21 days of age. The current study showed the expression of AvBD1 to 13 in the kidney of 3-day and 10-day-old chicks.…”
Section: Discussionmentioning
confidence: 98%
“…Fourteen AvBDs have been identified to date, and their expression has been shown in many tissues such as leukocytes, reproductive, digestive, and respiratory systems (Abdel Mageed et al, 2008, 2009; Cuperus et al, 2013 ; Yoshimura, 2015 ; Yoshimura and Barua, 2017 ). Although previous reports identified the expression of AvBDs in chicken kidneys ( Xu et al, 2015 ; Mowbray et al, 2018 ), the cells responsible for the expression of these proteins have not been identified.…”
Section: Introductionmentioning
confidence: 95%
“…7) экспрессия гена галлинацина-10 при скармливании пребиотика и пробиотика повысилась соответствен-но в 1,48 (p > 0,05) и 1,55 раза (p < 0,05). Всего у кур выявлено 14 генов дефензинов и галлинацинов, обладающих различной антимикробной активностью (38). В исследованиях на бройлерах при заражении Salmonella enterica наблюдалось подавление экспрессии генов галлинацина-10, галлинацина-11, галлинацина-13 и галлинацина-14, тогда как у генов дефензинов 1, 2, 7, 8 и 9 экспрессия осталась без изменения.…”
Section: экспрессия генаunclassified